Parenting Fatigue, Sexual Intimacy, and Religious Coping Strategies: A Critical Review - Agrawal, Stuti; Dubey, Anubhuti (Journal of Psychological Perspective, 2025)
Parenting fatigue is a multifaceted phenomenon characterized by chronic physical, emotional, and psychological exhaustion stemming from the unrelenting demands of raising children. This critical review synthesizes empirical findings on the intersections of parenting fatigue, sexual intimacy, and religious coping strategies, with particular attention to cultural and gender dynamics. Results consistently indicate that elevated levels of parenting fatigue correlate with decreased marital satisfaction, diminished libido, and weakened emotional connectivity between partners, often intensifying the risk of long-term relational and mental health complications. Although religious coping—through prayer, communal worship, and faith-based practices—can alleviate stress and bolster resilience, its effectiveness varies significantly across cultural contexts and personal beliefs. Many studies highlight a bias toward traditional family structures and maternal experiences, signalling a shortage of research on fathers, non-traditional families, and diverse religious or spiritual frameworks. The review also uncovers methodological gaps, including limited longitudinal research, insufficient cross-cultural comparisons, and an overemphasis on adverse outcomes to the neglect of positive dimensions such as marital resilience and spiritual growth. Overall, this paper advocates for more inclusive, longitudinal, and culturally sensitive investigations and integrated interventions addressing mental and sexual health. By illuminating the complexity of parenting fatigue and its ripple effects on sexual intimacy and coping mechanisms, this review offers valuable insights for designing culturally attuned mental health and family interventions that holistically support parents and couples. Clinicians can leverage this evidence to develop integrative therapeutic approaches, while policymakers can use it to inform inclusive programs that strengthen diverse family structures—promoting both psychological well-being and relational health.